Potential use of Claroideoglomus etunicatum to enrich signal grass (Brachiaria decumbens Stapf.) for silvopasture preparation - Risa ROSITA; Rahayu WIDIASTUTI; Irdika MANSUR; Sarah Asih FAULINA (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2020)
Silvopasture system improvement in managing post-mining land resources has been done by searching for a quality grass. One of the selected grass species is signal grass (Brachiaria decumbens Stapf.). This research aimed to prepare signal grass through the inoculation of AMF Claroideoglomus etunicatum, as an effort to enrich its growth before being applied to post-mining soil. Research stages included the AMF inoculation on signal grass through spore culture and then transferred the colonized grass to the pot using sterile zeolite as a growth medium. The treatment on the first stage was without and with AMF inoculation (dose of 20 spores) on signal grass which was repeated for 12 times. Incubation in a spore culture was 4 weeks while incubation in a pot containing sterile zeolite medium was 8 weeks. Research data were analyzed using the Shapiro-Wilk’s normality test, Independent Sample T-test, and Pearson’s correlation test. Observation results showed that the inoculation of C. etunicatum on signal grass was significantly impact on the increase of plant height, stem diameter, number of leaves, number of tillers, shoot and root fresh weight, and shoot dry weight (p <0.05). Microscopic observation showed that there was AMF colonization on treated signal grass roots in the amount of 55 ± 0.06 % with number of spores was 252 ± 9.82 per 10 g zeolites, while AMF infection was not found in uninoculated signal grass. It is expected that by providing signal grass inoculated with AMF C. etunicatum would support its growth in post-mining land for Silvopasture system.